Rapid, label‐free antibiotic susceptibility determined directly from positive blood culture. Issue 7 (22nd April 2022) - Filbrun, Alexandra B.; Richardson, Joseph C.; Khanal, Prakash C.; Tzeng, Yih‐Ling; Dickson, Robert M.
Abstract: Bacterial bloodstream infections are a significant cause of global morbidity and mortality. Constrained by low bacterial burdens of 1–100 colony‐forming‐units per ml blood (CFU/ml), clinical diagnosis relies on lengthy culture amplification and isolation steps prior to identification and antibiotic susceptibility testing (AST). The resulting >60‐h time to actionable treatment not only negatively impacts patient outcomes, but also increases the misuse and overuse of broad‐spectrum antibiotics that accelerates the rise in multidrug resistant infections. Consequently, the development of novel technologies capable of rapidly recovering bacteria from blood‐derived samples is crucial to human health. To address this need, we report a novel bacterial recovery technology from positive blood cultures that couples selective hemolysis with centrifugation through a sucrose cushion to perform rapid, background‐free cytometric ASTs without long subculturing steps. Demonstrated on the most common bloodstream infection‐causing bacteria: Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus, near‐pure bacteria are rapidly recovered (≤15 min) with minimal user intervention. Susceptibilities of recovered bacteria are readily performed via high throughput flow cytometry with excellent agreement with much slower, standard microbroth dilution assays. Altogether, this novel direct‐from‐positive blood culture AST technology enables susceptibility determinations within as little as 5 h, post blood culture positivity.